SISTEM INFORMASI PENGELOLAAN DAN PELAYANAN CENTRAL LAUNDRY RANTAUPRAPAT BERBASIS WEB - Neni Kemala Sari; Abdul Karim (Hexagon Jurnal Teknik dan Sains, 2020)
Today, the rapid development of the world of technology and information, spurred labor professionals, and layers of society, around the world to explore and develop their potential to keep up with these developments. Based on research on AZKI LAUNDRY Rantauprapat not yet look optimal and is still less efficient and not yet effective. The design of information systems in AZKI LAUNDRY Rantauprapat using the PHP Programming Language and MySQL. The design process starts from formulating the problem, setting goals, and collecting data. After all the required data is obtained, the design process is continued at the system analysis and software requirements stage. The result of this design is an application for the expected data processing process and represents the design that has been made. This application can perform the relevant process.